DINAMIKA KADAR NITRIT OKSIDA SELAMA STIMULASI KARBONDIOKSIDA DAN COLD PRESSOR TEST PADA PASIEN MIGREN - Yudy Goysal, Amiruddin Aliah, Irawan Jusuf (Neurona Majalah Kedokteran Neuro Sains, 2013)
INTRODUCTION MIGRAINE HAS NOW BEEN ASSOCIATED WITH ISCHEMIC STROKE WHICH IS SUBCLINICALLY SCREENED BY AUTOREGULATION DYSFUNCTION ENDOTHELIAL DYSFUNCTION MAY BE A MECHANISM UNDERLYING THIS ASSOCIATIONTHE STUDIESHOWS THAT NITRIC OXIDE NORELEASE IS IMPAIRED IN MIGRAINE PATIENTS